Metformin efficacy and tolerance according to genetic polymorphisms of organic cation transporter 1 in Tunisian patients with type 2 diabetes - Chaker, Fatma; Kallel, Ameni; Khessairi, Nadia; Yazidi, Meriem; Oueslati, Ibtissem; Chatti, Hiba Allah; Feki, Moncef; Chihaoui, Melika (Frontiers in Endocrinology, 2025)
PurposeMetformin efficacy and tolerance vary at equivalent dose in type 2 diabetes. Inter-individual variability in the response to metformin with approximately 35% of patients failing to achieve initial glycemic control may be explained by genetic polymorphisms that affect the drug’s pharmacokinetics and pharmacodynamics. Differences in the frequencies of pharmacogenomic risk alleles associated with metformin response may also account for interethnic variability in drug effects. The aim of this study was to assess the impact of M420del, R61c, and G401S polymorphisms in the SLC22A1 gene which encodes the organic cation transporter (OCT1) on metformin response and tolerance in a cohort of Tunisian patients with type 2 diabetes.MethodsThis prospective study included 73 newly diagnosed type 2 diabetic patients. Clinical and biological assessments were conducted before and three months after initiation of metformin therapy. Patients were genotyped for the M420del, R61c, and G401S polymorphism of SLC22A1 using Polymerase Chain Reaction (PCR) followed by Restriction Fragment Length Polymorphism (RFLP) analysis. Metformin efficacy was defined as an HbA1c reduction of ≥ 1% and metformin- induced gastrointestinal adverse effects were recorded using a questionnaire.ResultsThirty-nine patients (53%) were classified as responders to metformin. The M420del, R61C and G401S variants were not significantly associated with metformin efficacy (p: 0.8, p: 0.77, and p: 0.49 respectively). Twenty-seven patients (37%) experienced gastrointestinal adverse effects following metformin initiation. The G401S polymorphism and the haplotype (NoDel) CA were significantly associated with gastrointestinal adverse effects.ConclusionIn Tunisian type 2 diabetes, the M420del and R61C do not appear to be associated with metformin efficacy or the gastrointestinal intolerance. However, the G401S polymorphism may be implicated in the occurrence of metformine-induced gastrointestinal adverse effects.